PENERAPAN MODIFIED VOGEL'S APPROXIMATION METHOD (MVAM) UNTUK MEMINIMUMKAN BIAYA TRANSPORTASI (STUDI KASUS: PABRIK TAHU TAUFIK) - Marie Afiani; Susi Setiawani; Toto Bara Setiawan (Department of Mathematics, Hasanuddin University, 2020)
This research aims to determine the tofu product distribution transportation model at Taufik Tofu Factory. This type of research is applied research with a quantitative approach. The method used to solve transportation problems in this study is the Modified Vogel’s Approximation Method (MVAM) and optimized using the Modified Distribution (MODI) method. The results of this study indicate that the application of MVAM at the Taufik Tofu Factory provides a more minimum solution for calculating transportation costs, both in equilibrium and non-equilibrium problems. MVAM provides the same transportation costs as the optimal solution for the simplex method, which is equal to Rp1.164.911,00 for equilibrium problems and Rp2.176.838,00 for unequal problems. These results have been tested for optimism using MODI and better than the real cost calculations issued by the factory.